Pengaruh Technology Acceptance Model terhadap Sikap dan Kepuasan Pengguna Pada Sistem Core Banking (Studi Pada PT. Bank Pembangunan Daerah Kalimantan Selatan Kantor Cabang Utama Banjarmasin) - Irfan Syarif Wahyudi; Irwansyah Irwansyah; Setio Utomo (JURNAL BISNIS DAN PEMBANGUNAN, 2016)
This study aims to examine the Influence of Technology Acceptance Model Attitude and Kepuasanan Users within the Mandatory Use. Technology Acceptance Model (TAM) using two variables, ie variables and variable Kemanfatan Ease. Subjects in the study is the Bank's employees in South Kalimantan Main branch. as many as 74 employees. Measurement of variables using Likert scale techniques. Analysis of data using multiple linear regression statistical techniques and to test the significant level using the t test with SPSS. The results indicate that the effect of variable partial benefit against attitude to the influence of 7.7%. V ariabel user convenience not significant effect on attitudes. Attitudinal variables not significant effect on user satisfaction. Variable benefit significantly influence the attitude of the employees of PT. Regional Development Bank of South Kalimantan. It is shown from the regression coefficient that is 20.1%   Keywords: Technology Acceptance Model, Benefits, Ease Users, Attitude, User Satisfaction, mandatory use, core banking system